2018
DOI: 10.1007/s10753-018-0843-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Alleviates the Inflammatory Response Induced by LPS Through Inhibition of NF-κB/MAPKs-CCL2/CXCL1 Signaling Pathway in Cultured Astrocytes

Abstract: The purpose of this study was to investigate the inhibition neuroinflammation mechanisms of hyperbaric oxygen therapy (HBOT). Primary astrocytes were incubated with lipopolysaccharide (LPS) after which they underwent HBOT and separate administration of inflammatory cytokine inhibitors. The respective expression of inflammatory factors was then detected. Results showed that LPS significantly induced increases in the expression levels of chemokine (C-X-C motif) ligand 1 (CXCL1), chemokine C-C motif ligand 2 (CCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Alternatively, the p38 inhibitor had no obvious effect on expression levels of CCL2 and CXCL1. We further demonstrated that HBOT inhibited neuroin ammation via suppression of LPS-induced MAPK (JNK and ERK)/NF-κB-CCL2/CXCL1 signaling pathways in astrocytes [11]. In this study, a TRAF6 siRNA downregulated the expression levels of CCL2, CXCL1, p-NF-κB, p-JNK, p-ERK, and p-p38 in cultured astrocytes activated by LPS.…”
Section: Traumatic Brain Injury In Rats Signi Cantly Upregulated the supporting
confidence: 50%
See 2 more Smart Citations
“…Alternatively, the p38 inhibitor had no obvious effect on expression levels of CCL2 and CXCL1. We further demonstrated that HBOT inhibited neuroin ammation via suppression of LPS-induced MAPK (JNK and ERK)/NF-κB-CCL2/CXCL1 signaling pathways in astrocytes [11]. In this study, a TRAF6 siRNA downregulated the expression levels of CCL2, CXCL1, p-NF-κB, p-JNK, p-ERK, and p-p38 in cultured astrocytes activated by LPS.…”
Section: Traumatic Brain Injury In Rats Signi Cantly Upregulated the supporting
confidence: 50%
“…A sham operation group underwent the same surgical procedure but did not receive experimental TBI. Culture of primary cortical astrocytes Primary astrocyte cultures were prepared from the cerebral cortices of neonatal rats [11,21,22] purchased from the Experimental Animal Center of Nantong University. Bilateral cerebral cortices were isolated and transferred to ice-cold D-Hank's buffer.…”
Section: Animals and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Primary astrocyte cultures were prepared from the cerebral cortices of neonatal rats (Gao et al, 2009;Lu et al, 2014;Liu et al, 2018) purchased from the Experimental Animal Center of Nantong University. Bilateral cerebral cortices were isolated and transferred to ice-cold D-Hank's buffer.…”
Section: Culture Of Primary Cortical Astrocytesmentioning
confidence: 99%
“…We further demonstrated that in vitro administration of pro-inflammatory lipopolysaccharide (LPS) significantly upregulated expression levels of CCL2 and CXCL1 as well as phosphorylation (activation) of the stress-associated transcription factor nuclear factor-kappa B (NF-κB) and the mitogen-activated protein kinases (MAPKs), c-jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and p38 in cultured astrocytes prepared from cerebral cortices of neonatal rats. Conversely, neuroinflammation was modulated via regulation of LPS-induced MAPK/NF-κB-CCL2/CXCL1 signaling pathways (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%